Manuscripts of the Latin Classics 800-1200 - Kwakkel, Erik, 1970-; Project Muse; Project Muse. (Project Muse, 2016)
This book brings together six expert contributors to examine the production and use of medieval manuscripts containing classical Latin texts. The contributors consider everything from the physical qualities of the manuscripts to what we can learn about how their readers used and interacted with them; ultimately, they also make a case for the value of studying not just specific classical manuscripts, but distinct groups of them, showing how such a collective approach can add to our understanding of how they functioned in medieval society.
Manuscripts of the Latin classics : 800-1200 : an introduction / Erik Kwakkel -- Carolingian scholarship on classical authors : practices of reading and writing / Mariken Teeuwen -- The transmission of Tibullus in the tenth and eleventh centuries / Robert G. Babcock -- Diagrams of knowledge and rhetoric in manuscripts of Cicero's De inventione / Irene O'Daly -- Classics on scraps : classical manuscripts made from parchment waste / Erik Kwakkel -- Living with Ovid : the founding of Arnulf of Orleans' Thebes / David T. Gura -- William of Malmesbury and the classics : new evidence / Rodney Thomson.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Manuscripts, Latin (Medieval and modern); Electronic books; Electronic books